Meeting the needs of young Latino gay, bisexual, and other men who have sex with men (MSM) and transgender women living with HIV through the weCare intervention in the United States (US). - Alonzo, Jorge (EHQUIDAD, 2021)
OBJECTIVE: Young gay, bisexual, and other MSM (men who have sex with men) and transgender women in the United States (US) who are living with HIV, and particularly those who are Latino, have low rates of viral suppression. The weCare intervention uses social media to increase HIV care engagement. METHOD: We used community-based participatory research to develop the intervention as well as theory-based social media messages tailored to each participant’s unique context. We analyzed elements and characteristics of weCare, messages sent by the Cyber Health Educator (CHE), and lessons learned to meet the needs of Latino participants living with HIV. RESULTS: We identified 6 core elements, 5 key characteristics, effective social media messages used in implementation, and 8 important lessons regarding relationships between the CHE and HIV clinics, the CHE and participants, and participants and the health system. CONCLUSIONS: Social media offers a promising platform to retain young Latino gay bisexual and other MSM and transgender women living with HIV in care and achieve viral suppression.